Persepsi Pasien DM Tipe 2 Terhadap Penggunaan Obat Antidiabetes Oral di RSUP Dr. Hasan Sadikin Bandung - Eko Kuncoro Manunggaling Gusti; Kuswinarti Kuswinarti; Anisah Dahlan (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Type 2 Diabetes Mellitus (T2DM) is a lifelong metabolic disorder characterized by hyperglycemia, which requires continuous therapy. Oral antidiabetic drugs (OAD) become the main line in T2DM therapy. There are several factors influencing drug compliance and consumption, one of them is perception. Perception is a process of processing sensory information to form a meaning that will make T2DM patient take a decision to take the medication regularly and continously. The purpose of the study is to determine the perception of T2DM patients about the use of OAD in the Endocrine Polyclinic, Dr. Hasan Sadikin General Hospital, Bandung. This study uses categorical descriptive method with cross-sectional design. Data is collected using a questionnaire that has been through the process of validity and reliability tests. Sampling was done by convenience sampling method to 46 respondents. The variables in this study are respondents' characteristics and perceptions, which is grouped into four categories. The data was processed using the Rasch Model to be categorized into positive and negative perceptions based on the mean logit respondent value. The results showed positive perception of treatment benefits is 73.91%, positive perception of drug consumption procedures is 78.26%, positive perception of treatment side effects is 82.61%, and positive perception of drug consumption encouragement is 67.39%. Overall, the perception of T2DM patients about the use of OAD in RSHS is a positive perception. This is a good foundation for patients for doing the therapy regularly and continuously.